PENGARUH PELAKSANAAN PELATIHAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (STUDI KASUS KARYAWAN LAPANGAN PADA ENERGI MEGA PERSADA BENTU LTD) - Wandika, Cindi Tantia; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted at Energi Mega Persada Bentu Ltd with the problem in the study being the low performance of employees. The purpose of this study is to determine and analyze the effect of implementing training and organizational culture on employee performance partially and simultaneously. This study used a questionnaire as a data collection tool that was distributed to 51 respondents in Energi Mega Persada Bentu Ltd field employees. The data is then processed using descriptive analysis and quantitative analysis using SPSS by validating, reliability testing, simple linear regression analysis, multiple linear regression analysis, determination analysis and hypothesis testing by t test and F test.The results showed that the first hypothesis testing was the implementation of training on employee performance, namely t arithmetic (5.175)> t table (2.001), meaning that training has a significant effect on employee performance. Second, organizational culture, namely t arithmetic (7,616)> t table (2,009), meaning that organizational culture has a significant effect on employee performance. F test results (29.746)> F table (3.19) means the implementation of training and organizational culture simultaneously have a significant effect on employee performance.Keywords: Implementation Of Training, Organizational Culture, Employee Performance